(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The MMA fight between Khabib Nurmagomedov (Russia) and Connor McGregor (Ireland), organised by UFC 229 and held on 6 October 2018, was one of the most important sporting events of the year and is considered the most important fight in the history of the UFC (Ultimate Fighting Championship)[1]. The fight concluded with a victory for Khabib. After the event, the Russian fighter and one of the Irishman’s coaches (Dillon Danis) got into a verbal altercation that escalated into the former jumping out of the octagon and attacking the coach. This sparked a general brawl that involved part of the audience and members of both teams, inside and outside the octagon. In the press conference held immediately afterwards, as well as in subsequent appearances, Khabib justified[2] his behaviour by referring to McGregor’s previous actions and criticisms against him, repeatedly stating: “You cannot talk about religion or nations. You cannot talk about this stuff. This, for me, is very important”. I will stress the sentence that Khabib used most often, up to three times: “You cannot talk about religion”. His words marked the end of that extraordinary day, reflecting not only the intensity of the confrontation but also the tensions and divisions that currently characterise moral debate and its limits in a pluralistic society, specifically when freedom of speech is exercised to criticise certain aspects of religion, Islamic religion in particular. This violent episode, along with its subsequent justification (at various levels), highlighted the difficulty of having a constructive public debate in which differences can be discussed without overstepping the boundaries of dialogue.